Emergence of Neo-imperialism and The Perils Confronting Natural Resources of Developing Nations - Roka, Krishna (Dhaulagiri Journal of Sociology and Anthropology, 2006)
DOI: 10.3126/dsaj.v1i0.291 Dhaulagiri Vol.1 (2005) pp.207-219